Kepemimpinan Pemerintahan Legalistik dan Humanistik - Jeddawi, Murtir; Bakri, Riani; Husain, Muh Fachril (Jurnal Pallangga Praja (JPP), 2023)
Leadership has an important role in utilizing existing resources to realize organizational goals. That the existence of law enforcement cannot be separated from the regulatory function of a government leadership mechanism, so that the study of the form of government leadership from a legalistic and humanistic perspective is always interesting to discuss. The substance of leadership is making decisions, and making these decisions is of course through fair and humane communication between parties. This condition will only arise when the legal system and social order are enforced. In line with this, humanistic government becomes a relevant and urgent concern when dealing with government functions. Humanistic government focuses on, apart from the legalistic dimension, also the dimension of democratization and the wisdom and culture of society that lives and is practiced in people's lives according to the values of Pancasila and not on a rigid and formal approach to power based on authority.